A Slip-Line Approach to the Micro-Cutting Process with a Rounded-Edge Tool - Uysal, Alper; Ozturk, Sabri; Altan, Erhan (TRANS TECH PUBLICATIONS LTD, 2012)
The effect of tool edge roundness attracts growing attention due to increasing applications of precision, micro- and nano-machining technologies. A new slip-line model and its associated hodograph are proposed for cutting with a rounded-edge tool in this paper. New model considers stagnant metal region called as dead metal zone formed in front of the rake face of tool during cutting process. Dewhurst and Collins's [1] matrix technique for numerically solving the slip-line problem is employed in the mathematical formulation of the new model. The unknown slip-line angles were solved depending on the force data obtained from experiments and variation of the sub-regions with cutting edge radius was determined.
Keywords: slip-line; rounded-edge tool; micro-cutting; dead zone; FIELD SOLUTIONS; CONTACT; Engineering; Materials Science